Finding the path: Necessary corrections to incorporate the idea of the new library into the essential elements of citizenship - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2017)
The economic crisis has been harmful for libraries. Although the studies that have been done by professional associations have given evidence of their economic and social value, the reasons given to justify budget cuts and closures show that the real problem is not an economic problem but one of perception: Politicians and citizens give libraries a secondary place when competing with other basic services for financing. Everyone recognizes the past importance of libraries, but few situate them in contemporary education, information, and knowledge. The future of libraries depends mostly on what people think of them. Professionals can help to build a new popular awareness that places value on the idea of the library´s utility and neutralizes its presumed digital obsolescence. In this sense, technology is changing the role that institutions play, as well as the space that they have traditionally occupied. Technology has also changed our expectations towards institutions. In order to make the library something appealing and useful, the librarian must be able to facilitate the interconnection (cooperation, networking, benchmarking, and co-creation) and seek to reduce the barriers between the library as an institution and the users.
Keywords: Public Library; Values; Social imaginary; Society; Librarians; Roles.